(untitled) (LAPAI JOURNAL OF NIGERIA HISTORY, 2024)
This paper is a critical and objective assessment of the 2011 Post-Presidential Election Violence in Northwestern Nigeria with particular reference to Kaduna Metropolis. The place and significance of election in ensuring smooth transition from one government to another in any given society cannot in any way be underestimated. However, despite the improvements in the electoral process by INEC, there were still incidents of violence, hijacking and stealing of ballot boxes by party thugs, inflation of results and reports of police misconduct, particularly in southeastern Nigeria where official results in the presidential election in some rural areas recorded close to a 100 percent voter turnout. Oral interviews played vital role in carrying out this study because it is within the contemporary period and hence, the actors and factors that have shaped the events in question are so much around. In addition, secondary sources like books, journals and online resources were also perused. Thus, this paper argues that though this met with the rather tensed situation in Kaduna metropolis (an area that has experienced series of ethnoreligious violence – the last one being in 2002), it is discovered that these violent politicallyrelated conflicts and crises have brought about wanton destruction of human and material resources, population dislocation as well as the continuous search for common identity by the diverse people of the metropolis and the state at large leading to the final segregation of the town between a Christian dominated south and Muslim dominated north. However, continuous interfaith dialogue, provision of government facilities and infrastructures including housing where people irrespective of their faith could reside, an overhaul of the Nigerian justice system, implementations of reports of committees of inquiry among other things would go a long way in fostering unity and harmonious co-existence.